(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bandopadhyay’s writing was inspired by both Marxian philosophy and Freudian philosophy - which are quite contrasting in nature. His writing stands in stark contrast to that of other contemporary luminaries like Bibhutibhushan Bandopadhyay who portrayed life in rural Bengal in a gentle, lyrical light. Although he had some common grounds with Tarashankar Bandopadhyay, he distinguished himself with profound and rational analysis of the lives of ordinary people. Manik’s writing dealt with the pettiness and wretchedness of existence in the context of rural Bengal. His primary concern was the dark alleyways of the human mind, even among the supposedly simple village folk, and not the serene beauty of nature that was always in the background in his novels.